Combined methane reforming by carbon dioxide and steam in proton conducting solid oxide fuel cells for syngas/power co-generation. (7th June 2019) - Chen, Bin; Xu, Haoran; Zhang, Yuan; Dong, Feifei; Tan, Peng; Zhao, Tianshou; Ni, Meng
Abstract: Methane and carbon dioxide mixture can be used as the fuel in a proton conducting solid oxide fuel cell (SOFC) for power/syngas co-generation and greenhouse gas reduction. However, carbon deposition and low conversion ratio are potential problems for this technology. Apart from using functional catalytic layer in the SOFC to enhance CH4 dry reforming, adding H2 O into the fuel stream could facilitate the CH4 conversion and enhance the co-generation performance of the SOFC. In this work, the effects of adding H2 O to the CO2 CH4 fuel on the performance of a tubular proton conducting SOFC are studied numerically. Results show that the CH4 conversion is improved from 0.830 to 0.898 after adding 20% H2 O to the anode. Meanwhile, the current density is increased from 2832 A m −2 to 3064 A m −2 at 0.7 V. Sensitivity studies indicate that the H2 :CO ratio can be effectively controlled by the amount of H2 O addition and the H2 starvation can be alleviated, especially at high current density conditions. Highlights: Methane co-reforming for proton conducting solid oxide fuel cell is studied. H2 O addition into CH4 /CO2 mixture enhances fuel cell power output. The H2 and CO ratio can be controlled by H2 O addition and current density. Higher fuel flow rate decreases fuel cell performance.